Impulse Oscillometry System in pediatrics: review - Assumpção, Maíra S. de; Gonçalves, Renata M.; Ferreira, Letícia G.; Schivinski, Camila I.S. (Medicina (Ribeirao Preto), 2014)
Introduction: impulse oscillometry (IOS) is considered a method of evaluation of respiratory mechanics, and being non-invasive, has been increasingly mentioned in the care and research of pediatric patients. Studies have considered the interest of determining reference values and check the IOS relationship with other methods of respiratory assessment.Objective: to present an update of the literature regarding the system, technical criteria and interpretation of data, as well as the relationship of the system with other methods of respiratory assessment and its clinical applicability.Method: literature review with consultation in the databases MEDLINE / PubMed and Ebsco, using the keywords: “impulse oscillometry”, "reference  values” and “child”. It was considered all material with information about the equipment, their indications and application as an evaluation tool in different clinical situations.Results: 45 documents were identified, (41 trials and 4 reviews), supplemented with 20 papers (1 guideline, 1 manual on equipment and 18 articles on the subject). This material was characterized by approaching the equipment, its parameters evaluation, performance technique and positioning of the patient during the examination, criteria for acceptability and reproducibility, and interpretation of the data obtained. There are several publications of this tool in the evaluation of respiratory mechanics disorders such as asthma and cystic fibrosis, and making on reference values in healthy children. Conclusion: IOS is a relatively new feature, whose indication  in pediatrics has been increasing, but still required investigations, both technical and clinical investigations.